A review of preparation methods of porous skin tissue engineering scaffolds. (August 2022) - Zhang, Zefei; Feng, Yihua; Wang, Li; Liu, Dongxue; Qin, Changcai; Shi, Yanbin
Abstract: In recent years, preparation technology for tissue-engineered scaffolds has continuously improved; researchers can select suitable preparation methods according to the scaffold requirements. A skin-tissue scaffold must have a porous structure; the structure affects wound healing, hydrophilicity, the degradation rate, and the mechanical properties of the scaffold, and acts as a nutrient and metabolites transportation channel for cell adhesion and growth, new tissue regeneration providing the space environment. Technologies including solvent casting/particle leaching, freeze-drying, electrospinning, 3-D bioprinting, and gas foaming have been used to prepare porous skin scaffolds. Preparation using these five methods is examined in this review. The optimization design and application of these methods are introduced; the advantages and disadvantages, and the future prospects of these methods are summarized. Graphical Abstract: The basic process of the five preparation methods and the basic structure of their holes are summarized. ga1